Transcription of genes involved in bacterio-opsin gene expression in mutants of a halophilic archaebacterium. - Leong, D (1988)
Recent studies on the regulation of the bacterio-opsin (bop) gene of the archaebacterium Halobacterium halobium suggest that the brp and putative bat genes are involved in bop gene expression or purple membrane assembly. These two genes are located 526 and 1,602 base pairs, respectively, upstream of the bop gene and are both transcribed in the opposite orientation to the bop gene. Transcription of the bop, brp, and putative bat genes was characterized in the wild type, 11 Bop mutants, and a Bop revertant by using a series of RNA probes. Quantitation of the relative mRNA levels for these three genes in the wild type revealed that the brp and bat transcripts are present at approximately 2 and 4%, respectively, of bop mRNA levels under the growth conditions used. Northern (RNA) blot analysis of Bop mutants indicated that insertions in the brp gene affect expression of the putative bat gene. In addition, deletion of most of the bat gene resulted in virtually undetectable levels of bop and brp mRNAs. These and other results lead us to propose that (i) brp gene expression can affect bat gene expression and (ii) the putative bat gene is involved in activating bop and brp gene expression.